ANALYSIS OF FACTORS AFFECTING PROFITABILITY Case Study of Manufacturing Companies in the Plastics and Packaging Sub-Sector Listed on the Indonesia Stock Exchange in 2019-2023: Case Study of Manufacturing Companies in the Plastics and Packaging Sub-Sector Listed on the Indonesia Stock Exchange in 2019-2023 - Nur Komarudin, Munir; Yusuf, Ayus Ahmad; Aji, Ibrahim (IJSM, 2025)
This study will analyze the Factors affecting the Profitability of Indonesia Stock Exchange (IDX) listed Plastic and Packaging Sub-Sector Manufacturing Companies between 2019-2023, Independent variables to be analyzed are External and Internal Factors affecting Company Profitability which are Exchange Rates, Inflation, BI Rate Interest Rates, Leverage and Company Size while Profitability is the Dependent Variable to be measured using Return on Assets (ROA). The analytical approach used is the Panel data Regression Model and the Coefficient of Determination via the Random Effect Model (REM) approach. The data in this study were gathered from the Financial Statements of the Plastic and Packaging Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the Period 2019-2023 using the Sampling Technique in this study using Purposive Sampling so that this study had a sample of 13 companies with 65 Financial Statement Data. The conclusion of this study indicates that BI Rate and Leverage Interest Rate have partially significant negative effects on profitability and Exchange Rate, Inflation and Company Size do not have partially significant negative effects on profitability. Meanwhile Exchange Rate, Inflation, BI Rate, Leverage and Company Size have Significant Impact on Profitability